FALSAFAH ETIKA BISNIS DALAM AL- QURAN - Eva Iryani (Jurnal Ilmiah Universitas Batanghari Jambi, 2014)
Al-Qur’an is the revelation which is reduced for many purpuses. One of the purposes is to vanish both material poverty and spiritual, foolish, illness and living suffer. Business ethic in Al-Qur’an is normative discipline, in which the certain ethic standard that has been formulated and then applied that will be the guidance in running business. The norm or ethic are also stated in Al-Qur’an and the prophet’s teaching, which discuss more deeply and broadly, also more comprehensively, that explains that Islam is emphasized more on the ethic, moral and attitude in every way of life, include also in it business ethic.